Remote W.A.R.A. Compared With Face-to-Face W.A.R.A.: A Pilot Study - Weerkamp-Bartholomeus, Paula; Marazziti, Donatella; van Amelsvoort, Therese (Frontiers in Psychology, 2021)
Background: Since the outbreak of the COVID-19 pandemic and its social restriction measures, online therapy is a life-saving possibility for patients with acute stress. Wiring Affect with ReAttach (W.A.R.A.) is a brief psychological intervention aiming to decrease negative affect, that can be offered online. Methods: We assessed the effect of remote W.A.R.A. on negative affect in 37 patients. Consequently, we compared the effect of remote W.A.R.A. versus face-to-face W.A.R.A on negative affect in a cross-sectional design. Results: W.A.R.A. remote therapy provoked a significant reduction of negative affect with a large effect size (d=3.08, p < 0.001). However, the reduction in negative affect was smaller than with W.A.R.A. face-to-face. We found a substantial difference between W.A.R.A. remote therapy and W.A.R.A. face-to-face in decrease of negative affect (d=1.36, p < 0.001). Limitations: We designed a numeric rating scale for evaluating negative affect. We investigated the impact on negative affect by assessing 'unpleasant feelings'. This conceptualization of negative affect might still be a point of discussion. Conclusions: The study's findings indicated that W.A.R.A. remote therapy significantly reduced negative affect, but to a lesser extent than W.A.R.A. face-to-face. Nevertheless, W.A.R.A. remote therapy might offer a fast relief, especially when personal contact is difficult.